Anticancer effects of anti-CD47 immunotherapy in vivo. (4th March 2019) - Iribarren, Kristina; Buque, Aitziber; Mondragon, Laura; Xie, Wei; Lévesque, Sarah; Pol, Jonathan; Zitvogel, Laurence; Kepp, Oliver; Kroemer, Guido
ABSTRACT: The treatment of breast cancer largely depends on the utilization of immunogenic chemotherapeutics, which, as a common leitmotif, stimulate the exposure of calreticulin (CALR) on the surface of cancer cells, thereby facilitating their recognition by dendritic cells for the uptake of tumor-associated antigens and subsequent antigen cross-presentation to cytotoxic T cells. Breast cancer cells also express the calreticulin antagonist CD47, which inhibits tumor cell phagocytosis and consequently subverts anticancer immune responses. Here, we treated carcinogen-induced or transplantable mouse models of cancer by a CD47 blocking antibody that was at least as efficient as chemotherapy and that could be favorably combined with the anthracycline mitoxantrone in the context of carcinogen-induced orthotopic breast cancers. Monotherapy by CD47 blockade led to a reduction in tumor growth and an increase in overall survival. Of note, this treatment lead to a moderate depletion of M2 macrophages as well as close-to-complete elimination of regulatory T cells from the tumor bed, suggesting a strong favorable impact of CD47 blockade on the tumor microenvironment.